2007
DOI: 10.1007/s11162-007-9079-y
|View full text |Cite
|
Sign up to set email alerts
|

Emerging from the Pipeline: African American Students, Socioeconomic Status, and College Experiences and Outcomes

Abstract: This study focuses on how social class affects the college experiences and outcomes for African American students in 4-year colleges and universities. Using a national, longitudinal data base, the findings indicate that low SES African American students have less contact with faculty, study less, are less involved with student organizations, work more, and have lower grades than do their high SES peers or all African American students. Furthermore, 9 years after entering college, low SES students report lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 32 publications
4
73
1
2
Order By: Relevance
“…Values are presented as estimated error/standard error. is consistent with findings from other studies (Judge & Hurst, 2007;Strenze, 2007;Walpole, 2008;Zagorsky, 2007). The lack of a significant relationship between gender and occupational aspirations shows that greater career achievement in later life could not be explained by boys' aspirations to more prestigious occupations, but that it must be due to other factors.…”
Section: Figure 2 Structural Model Of Adolescent Predictors Of Careersupporting
confidence: 91%
“…Values are presented as estimated error/standard error. is consistent with findings from other studies (Judge & Hurst, 2007;Strenze, 2007;Walpole, 2008;Zagorsky, 2007). The lack of a significant relationship between gender and occupational aspirations shows that greater career achievement in later life could not be explained by boys' aspirations to more prestigious occupations, but that it must be due to other factors.…”
Section: Figure 2 Structural Model Of Adolescent Predictors Of Careersupporting
confidence: 91%
“…Previous research has found that students' noncognitive characteristics, including their motivation and commitment to succeed academically, are significantly related to their grades in college Terenzini 1991, 2005;Sedlacek 2004; Thomas et al 2007;Williford 1996). Likewise a lack of knowledge about what is required for success in college has been shown to be negatively related to educational attainment (Szelényi et al 2007;Walpole 2008). Including measures that can serve as proxies for commitment, motivation, and knowledge frequently necessitates the use of self-report instruments such as entering student surveys.…”
Section: Methodsmentioning
confidence: 99%
“…Although studies have tried to link undergraduate GPA as a predictor of doctoral completion, Attiyeh (1999) and others (Hurtado, Inkelas, Briggs, & Rhee, 1997;Zwick, 1991) have shown that undergraduate GPA is not a valid predictor of doctoral degree completion. However, it has been shown that with a higher undergraduate GPA aspirations for a doctoral degree have increased (Walpole, 2006). Although undergraduate GPA may not be the best predictor of doctoral completion, already having attained a master's degree does appear to be a good academic aptitude indicator of doctoral degree completion.…”
Section: Academicsmentioning
confidence: 99%